1983
DOI: 10.1007/bf00275948
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of 5-hydroxytryptophan and 5-hydroxytryptamine on the function of microdissected ob/ob-mouse pancreatic islets

Abstract: The effects of 5-hydroxytryptamine and 5-hydroxytryptophan on insulin release and 45Ca2+ uptake in islets microdissected from ob/ob mice were studied. At a concentration of 4 mmol/l both compounds slightly stimulated insulin release at a low glucose concentration (3 mmol/l). Insulin release induced by 20 mmol/l D-glucose was inhibited by 4 mmol/l 5-hydroxytryptamine but potentiated by 4 mmol/l L-5-hydroxytryptophan. Mannoheptulose (20 mmol/l) blocked the combined effects of 20 mmol/l D-glucose and 4 mmol/l L-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The alkalinizing effect of glucose appears not to be secondary to increased insulin release. Both theophylline (Malaisse et al, 1967;Hellman et al, 1974) and L-5-hydroxytryptophan (Lindstr6m & Sehlin, 1983; see the Results section above) are strong potentiators of glucose-induced insulin…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The alkalinizing effect of glucose appears not to be secondary to increased insulin release. Both theophylline (Malaisse et al, 1967;Hellman et al, 1974) and L-5-hydroxytryptophan (Lindstr6m & Sehlin, 1983; see the Results section above) are strong potentiators of glucose-induced insulin…”
Section: Discussionmentioning
confidence: 97%
“…The [14C]DMO uptake at high glucose was further increased by 4mM-L-5-hydroxytryptophan to an apparent pHi of 7.53. We have previously shown that L-5-hydroxytryptophan is a strong potentiator of glucose-induced insulin release in experiments using bicarbonate-buffered media (Lindstr6m & Sehlin, 1983). In separate experiments we found that this is the case also in media devoid of bicarbonate buffer.…”
Section: Preincubation Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…SDAT has been suggested to be a gener-alized disease (34,35) and our present findings support this suggestion. Cholinergic and catecholaminergic substances play an important role in the modulation of insulin and glucagon release (33,36,37) which might explain the elevated insulin levels in our patients with SDAT.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have indicated that monoamines, such as 5-HT, DA, epinephrine, and norepinephrine, can inhibit glucose-mediated insulin secretion in human, golden hamster, rat, and mouse pancreatic islet B cells (Porte and Williams 1966;Feldman and Lebovitz 1970;Feldman et al 1971;Aleyassine and Gardiner 1975;Lindstrom and Sehlin 1983). The catecholamines, epinephrine and norepinephrine, can regulate insulin secretion directly (Porte et al 1976).…”
Section: Discussionmentioning
confidence: 99%